КИШИ ЖАСТАҒЫ МЕКТЕП ОҚЫЎШЫЛАРЫН МИЙНЕТКЕ ҚӘЛИПЛЕСТИРИЎ МАШҚАЛАЛАРЫ - Даўлетмуратова, Э.; Маткаримова, М.; Оңғарбаева, М. (FAN va JAMIYAT, 2018)
The article deals with peculiar features and beneficial methods in the preparation of the first-year students to labour education. Particularly the individual approach to every child among his/her classmates makes it possible to feel a sense of citizenship and self-becoming and leads him/her to a great progress.